Efforts to Increase Community Behavior Insights in Disposing of Garbage in Temporary Garbage Shelters in Singkawang City - Fajar Wulandari; Rika Wahyuni; Heru Susanto; Insan Suwanto (Islamic Studies Journal for Social Transformation, 2021)
The behavior and habits of residents in disposing of waste by not distinguishing between recyclable and nonrecyclable waste can lead to new problems. This paper is the result of community service to increase publicknowledge about environmental cleanliness in Singkawang City. The author sees the need for efforts to increasethis insight through action or by providing information about behavior in disposing of waste in temporary landfillsso that the problem of minimal waste can be reduced. Kegiatan is done by the method of socialization and is partof qualitative methods. Collecting data through a closed questionnaire which in this questionnaire has presentedanswers in such a way, so that respondents are asked to choose an answer that suits their characteristics by giving across or a checklist. The question-and-answer method is also used, this method makes the activity more interestingbecause of interactions such as explaining and followed by a question and answer session between the officers, thecommunity who are on-site, and the presenter. It is also hoped that this can add to the national insight of theparticipants who receive socialization about Disposing of Garbage in Temporary Garbage Shelters in SingkawangCity